Correlation of Environmental Vocabulary Mastery with News Text Writing Skills of Grade XI Students of SMA Negeri 2 Kinali - Mirna Wati; Ayu Gustia Ningsih (Raja Zulkarnain Education Foundation, 2026)
This study aims to determine the correlation of environmental vocabulary mastery with writing skills of class XI students of SMA Negeri 2 Kinali. This study was conducted at SMA Negeri 2 Kinali on class XI students which was held in January 2026. The population in this study were all class XI students of SMA Negeri 2 Kinali, totaling 169 people and the sample in this study were 34 class XI students taken using random sampling techniques. The instruments used in this study were objective and performance tests. The tool used to analyze the data was a correlational research formula assisted by Microsoft Excel. The mastery of environmental vocabulary in class XI students of SMA Negeri 2 Kinali was in more than sufficient qualifications (75.08). The skills of writing news texts of class XI students of SMA Negeri 2 Kinali were in good qualifications (76.72). Then the correlation of environmental vocabulary mastery with news text writing skills of class XI students of SMA Negeri 2 Kinali was analyzed using the product moment formula. Based on the results of the correlation calculation, the value of rhitung> rtable was 0.944> 0.339. The correlation is positive, which means the relationship between the two variables is parallel, namely the higher the mastery of environmental vocabulary in students, the higher the students' news text writing skills. The results of the hypothesis test show that the t count (16.174) is greater than the t table (2.034). Based on the results of the hypothesis test, it is concluded that H0 is rejected and H1 is accepted. Acceptance of H1 can be interpreted that there is a significant relationship between environmental vocabulary mastery and news text writing skills of class XI students of SMA Negeri 2 Kinali.